2016
DOI: 10.1007/s11356-016-8173-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of selenium pretreatment in the attenuation of lung injury in rats induced by fine particulate matters

Abstract: Selenium (Se) is vital for health because of its antioxidative and anti-inflammation functions. The aim of this study was to determine if dietary selenium could inhibit the rat lung injury induced by ambient fine particulate matter (PM). Sprague-Dawley rats were randomly allocated in seven groups (n = 8). The rats in PM exposure group were intratracheally instilled with 40 mg/kg of body weight (b.w.) of PM suspension. The rats in Se prevention groups were pretreated with 17.5, 35, or 70 μg/kg b.w. of Se for 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 58 publications
4
18
0
Order By: Relevance
“…Selenium (Se) is an essential trace element [ 1 , 2 ] that evinces antioxidant activity [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ], anti-inflammatory [ 2 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ], antimutagenic [ 26 , 27 ], anticarcinogenic [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] or chemopreventive [ 2 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ], antiviral [ 2 ], antibacterial [ 45 , 46 , 47 , 48 ], antifungal [ 49 , 50 ] and antiparasitic effects [ 51 ,…”
Section: Biochemistry Of Seleniummentioning
confidence: 99%
“…Selenium (Se) is an essential trace element [ 1 , 2 ] that evinces antioxidant activity [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ], anti-inflammatory [ 2 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ], antimutagenic [ 26 , 27 ], anticarcinogenic [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] or chemopreventive [ 2 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ], antiviral [ 2 ], antibacterial [ 45 , 46 , 47 , 48 ], antifungal [ 49 , 50 ] and antiparasitic effects [ 51 ,…”
Section: Biochemistry Of Seleniummentioning
confidence: 99%
“…Especially since both asthma and PM exposure have already been associated with a significant reduction in SOD or polymorphisms in genes implicated in the GSH system have been detected . Moreover, also dietary antioxidants, such as selenium, were already associated with reduced oxidative stress and lung inflammation in a model of PM‐induced lung injury . Furthermore, selenium supplementation improved symptoms in asthmatics compared to placebo …”
Section: Potential Therapeutic Targets In the Treatment Of Pollutant‐mentioning
confidence: 99%
“…In vivo research in mice, that is using specific knockout strains and monoclonal antibodies, can provide additional insights into potential mechanisms how air pollution can modulate (allergic) airway inflammation and offer the opportunity to validate hypotheses that have been generated by human studies. First, during acute DEPs-induced inflammatory lung responses, an increased expression of IL-1b 58,59,64,[169][170][171][172][173][174][175][176][177] and GM-CSF 139,178 in BALF and lung tissue were observed, whereas 1 study reported IL-25, IL-33 and TSLP as undetectable. 139 Moreover, the increased IL-1b and GM-CSF levels could be linked to PM or DEPs-induced inflammation and AHR.…”
Section: Particulate Matter and Type 2-promoting Cytokines: Expressmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduced diseases infection and mortality rate with organic and nano selenium supplementation could be attributed to the improvement in immunity response. Selenium (Se) is an essential trace element (Lu and Holmgren, 2009;Rayman, 2000) that evinces antioxidant activity (Abuelo et al, 2016;Dkhil et al, 2016;Lu et al, 2017;Ju et al, 2017), antiinflammatory (Aaseth et al, 2016;El-Ghazaly et al, 2017;Liu et al, 2017;Malhotra et al, 2016;Speckmann and Steinbrenner, 2014), antimutagenic (Peng et al, 2016;Schrauzer, 2008), anticarcinogenic (Ahmad et al, 2015;Hassan and Webster, 2016;Tran et al, 2010) or chemopreventive (Rao et al, 2001), antiviral (Hefnawy and Tórtora-Pérez, 2010) antibacterial (Cihalova et al, 2015;Guisbiers et al, 2016;Chudobova et al, 2014;Wang et al, 2015), antifungal (Guisbiers et al, 2017;Shakibaie et al, 2015) and antiparasitic effects (Beheshti et al, 2013;Dkhil et al, 2016;Mahmoudvand et al, 2014). Furthermore, it is an integral component of selenoproteins participating in a whole series of physiologically important processes (Pascual and Aranda, 2013).…”
Section: Health Status and Mortality Ratementioning
confidence: 99%